2020
DOI: 10.1371/journal.pone.0244676
|View full text |Cite
|
Sign up to set email alerts
|

3D visual cueing shortens the double support phase of the gait cycle in patients with advanced Parkinson's disease treated with DBS of the STN

Abstract: Background Gait disturbances have emerged as some of the main therapeutic concerns in late-stage Parkinson’s disease (PD) treated with dopaminergic therapy and deep brain stimulation (DBS). External cues may help to overcome freezing of gait (FOG) and improve some of the gait parameters. Aim To evaluate the effect of 3D visual cues and STN-DBS on gait in PD group. Methods We enrolled 35 PD patients treated with DBS of nucleus subthalamicus (STN-DBS). Twenty-five patients (5 females; mean age 58.9 ±6.3) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 44 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…It has been shown that the gait of PD patients differs from the gait of healthy controls in many motor aspects [4,[15][16][17][18][19][20]22,23]. Our MoCap-based research supports the findings and provides greater insight into the topic by unveiling relations that have not been fully considered hitherto.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…It has been shown that the gait of PD patients differs from the gait of healthy controls in many motor aspects [4,[15][16][17][18][19][20]22,23]. Our MoCap-based research supports the findings and provides greater insight into the topic by unveiling relations that have not been fully considered hitherto.…”
Section: Discussionsupporting
confidence: 76%
“…The extended DST is viewed as a pattern of disrupted gait control (in PD, it extends when in OFF state [17] and shortens when 3D cueing is provided [4]). The extension in the PD patients often breaks physiological ratio of SST:DST (4:1) [4, [15][16][17][18][19]; according to a meta-analysis [20], it changes to 3.93:1.08.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Below, data are reported as mean ± SD. Twenty trials (Arias and Cudeiro, 2010;Barthel et al, 2018;Beck et al, 2015;Bryant et al, 2010;Bunting-Perry et al, 2013;Cao et al, 2020;Cubo et al, 2003;Gál et al, 2019;Holmes et al, 2015;Horin et al, 2020;Kompoliti et al, 2000;Lebold and Almeida, 2010;Lee et al, 2012;Rosenthal et al, 2018;Poláková et al, 2020;Sijobert et al, 2017;Willems et al, 2006;Stuart et al, 2021;Zhao et al, 2016;Janssen et al, 2017) assessed cueing effectiveness on FOG exclusively during walking tasks, while one study (Russo et al, 2022), tested the effect of cues during gait initiation and walking. The total sample was 353 PD patients with FOG with an overall mean age of 69.8 ± 7.9 years.…”
Section: Studies Overviewmentioning
confidence: 99%